Morphofunctional features of the esophageal tonsil in some wild and domestic bird species - V. Т. Khomich; S. І. Usenko; N. V. Dyshliuk (Regulatory Mechanisms in Biosystems, 2020)
It is well known that the esophageal tonsil belongs to the peripheral immune system of birds. Its functional basis is formed by lymphoid tissue, in which, under the influence of antigens, lymphocytes differentiate into effector cells, causing specific immunity. Material for histological research was selected from adults of 18 species of wild and domestic birds, belonging to 6 orders. When performing the experiment, the classical methods of staining histopreparations with hematoxylin and eosin, according to Mallory, Van Gieson, were used and impregnated with argentic nitrate according to Kelemen. The object for cytological, electron microscopic and immunohistochemical studies was the esophageal tonsil of G. gallus. In the course of this work it was demonstrated that the esophageal tonsil is located in the mucous membrane and submucosa of the junction between the caudal part of the esophagus and the glandular stomach (proventriculus). Most of the examined bird species (Galliformes – G. gallus, N. meleagris, C. coturnix, M. gallopavo, P. colchicus, B. bonasia, P. сrictatus; Anseriformes – A. platyrhynchos, A. anser, B. сanadensis; Passeriformes – P. рica, C. сornix; Ciconiiformes – C. ciconia) have an esophageal tonsil which was detected macroscopically. It has an annular shape, a plicated and uneven surface with holes of crypts and light pink colour. Its size is different in the birds of the studied species. It was recorded that the greatest length is in B. canadensis and C. ciconia, and the smallest is in C. coturnix and Р. pіса, the maximum width is in A. platyrhynchos, and the minimum width is in P. pica and C. cornix. In L. lagopus (Galliformes), G. glandarius (Passeriformes), G. сhloropus, F. аtra (Gruiformes) and C. livia (Columbiformes) the esophageal tonsil is not macroscopically visible. Most birds of the examined species have tonsils apposing directly with the glandular part of the stomach. Only A. anser and B. canadensis have a transition zone between them, the morphology of which differs from that of the tonsils and the glandular part of the stomach. Lymphoid tissue in birds of most species is represented by all levels of structural organization. It occupies the largest area in the tonsil of A. platyrhynchos and the smallest in L. lagopus. The area of lymphoid tissue and its location are different in the birds of the examined species. According to this criterion it is proposed to classify the tonsils into compact and diffuse ones. Reticular cells, lymphocytes, immunoblasts, plasma cells, monocytes and macrophages have been identified in lymphoid tissue of esophageal tonsil of G. gallus. Among the lymphocytes their subpopulations were found that respond to monoclonal antibodies with markers CD4+, CD8+ and CD20+. CD34+cells were not found in the tonsil.